Vertically self-ordered orientation of nanocrystalline hexagonal boron nitride thin films for enhanced thermal characteristics - Cometto, Olivier (2018)
Vertically self-ordered hexagonal boron nitride (ordered h-BN) is a highly ordered turbostratic BN (t-BN) material similar to hexagonal BN, with its planar structure perpendicularly oriented to the substrate. The ordered h-BN thin films were grown using a High Power Impulse Magnetron Sputtering (HiPIMS) system with a lanthanum hexaboride (LaB6) target reactively sputtered in nitrogen gas. The best vertical alignment was obtained at room temperature, with a grounded bias and a HiPIMS peak power density of 60 W cm−2. Even though the film contains up to 7.5 at% lanthanum, it retains its highly insulative properties and it was observed that an increase in compressive stress is correlated to an increase in film ordering quality. Importantly, the thermal conductivity of vertically ordered h-BN is considerably high at 5.1 W m−1 K−1. The favourable thermal conductivity coupled with the dielectric properties of this novel material and the low temperature growth could outperform SiO2 in high power density electronic applications.